Enhanced Temperature Control Method Using ANFIS with FPGA. (4th March 2014) - Huang, Chiung-Wei; Pan, Shing-Tai; Zhou, Jun-Tin; Chang, Cheng-Yuan
Abstract : Temperature control in etching process is important for semiconductor manufacturing technology. However, pressure variations in vacuum chamber results in a change in temperature, worsening the accuracy of the temperature of the wafer and the speed and quality of the etching process. This work develops an adaptive network-based fuzzy inference system (ANFIS) using a field-programmable gate array (FPGA) to improve the effectiveness. The proposed method adjusts every membership function to keep the temperature in the chamber stable. The improvement of the proposed algorithm is confirmed using a medium vacuum (MV) inductively-coupled plasma- (ICP-) type etcher.